Confraternities of Indians and local power in colonial Peru: Huaraz, 17th century - Varón, Rafael (1982)
Faced with the powerful presence of the Catholic religion, the local native cults -that is, the most prestigious ones- had to undergo diverse and numerous transformations that, in the medium and long term, determined the survival of many elements of these native cults in Peruvian lands.